Islam and anthropology: opposition or harmony? - Md Yassin, Khairil Azhar (2012)
This paper represents a humble attempt made by the author in Islamizing anthropology. The paper intends, briefly, to conceptualize the basic issues in Islamization of social sciences with particular reference to anthropology. The basic issues, among others, include the relationship between Islam and anthropology, the foundation, and the sources in integrating Islamic principles in Western anthropology. Since the nature of this paper is introductory, it will attempt to delineate these three basic issues as simple as possible in order to present the approaches that Muslim anthropologists could adopt in their endeavor to inject Islamic values into the discipline. The author hopes to examine the main issues of the discussion in this article in a more coherent manner in the future.